'I am not a number': on quantification and algorithmic norms in translation. - Moorkens, Joss (Perspectives: Studies in Translatology, 2024)
Numbers and measurements enable transactions and communication in translation in ways that are helpful and indisputably necessary. However, as deployment of quantification and mathematisation has become more complex and opaque, it is important to interrogate the validity of measures and predictions, especially if they are to be used as a basis for action. This article takes a critical look at the various types of quantification and mathematisation used in translation and considers the effects of these on translators working in highly technologized workflows. It introduces the concept of algorithmic norms, whereby translators feel pressured to reverse engineer and conform to the demands of algorithmic management.